Changes of connective tissue biochemical indexes in children and adolescents with inflammatory diseases of joints - Шевченко, Н. С.; Лебець, І. С.; Кашкалда, Д. А. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
The biochemical parameters of connective tissue metabolism in children and adolescents with inflammatory diseases of joints have been studied. It has been shown that an essential feature of the state of connective tissue at rheumatoid and reactive arthritis in children and adolescents are metabolic changes of its structures, accompanied by a progressive loss of basic functionally important components of the extracellular matrix, but with a more pronounced pathological component at juvenile rheumatoid arthritis. The basic reflection of the development of dystrophic changes is the deficiency state of glycosaminoglycans (GAG), mainly due to GAG2 (chondroitin-4-sulfates and dermatan sulfates) and GAG3 (dermatan and keratan sulfates). Gender differences have been found, indicating a greater intensity of connective tissue metabolism in females.